2015
DOI: 10.1111/ced.12729
|View full text |Cite
|
Sign up to set email alerts
|

Calciphylaxis with evidence of hypercoagulability successfully treated with unfractionated heparin: a multidisciplinary approach

Abstract: Calciphylaxis is characterized by abnormal calcification of vessels and skin; however, its aetiology and pathogenesis remain unclear. Entities frequently associated with calciphylaxis are end-stage renal disease, diabetes mellitus, hypercalcaemia, hyperphosphataemia, elevated calcium-phosphate product, hyperparathyroidism and possible hypercoagulable states. Skin lesions may remain quiescent or may develop suddenly and progress rapidly. They are more common on the legs. Treatment of calciphylaxis is very chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Hypercoagulability has been posited as a potential risk factor for calciphylaxis . This hypothesis arose from numerous case reports and case series of patients with calciphylaxis with hypercoagulable conditions . Although descriptive studies have suggested that hypercoagulable states may predispose patients to calciphylaxis, lack of comparison to a control group has potential to overestimate the association.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercoagulability has been posited as a potential risk factor for calciphylaxis . This hypothesis arose from numerous case reports and case series of patients with calciphylaxis with hypercoagulable conditions . Although descriptive studies have suggested that hypercoagulable states may predispose patients to calciphylaxis, lack of comparison to a control group has potential to overestimate the association.…”
Section: Introductionmentioning
confidence: 99%
“…7 This hypothesis arose from numerous case reports and case series of patients with calciphylaxis with hypercoagulable conditions. [8][9][10][11][12] Although descriptive studies have suggested that hypercoagulable states may predispose patients to calciphylaxis, lack of comparison to a control group has potential to overestimate the association. It is noteworthy that thrombophilias are also present at high rates in patients with chronic kidney disease (CKD), a group that significantly overlaps with patients with calciphylaxis, further complicating study of hypercoagulable risk factors.…”
mentioning
confidence: 99%
“…Calciphylaxis patients treated with tissue plasminogen activator had approximately 30% greater survival than controls, but significant difference was not observed 11 . Therapeutic success in a case of calciphylaxis is thought to be associated with low molecular weight heparin for hypercoagulable condition 12 . Hence, as a potential risk factor, hypercoagulability plays an important role in the pathogenic mechanism and is proposed to be the treatment target for calciphylaxis.…”
Section: Dicussionmentioning
confidence: 99%
“…Although microvascular calcification is regarded as the basic histopathological characteristic, it is noteworthy that hypercoagulable states seem to be crucial in the development of CUA 6,10 , and anticoagulants including tissue plasminogen activator or low molecular weight heparin have been reported effective 6,[10][11][12] . We have reported an innovative therapeutic strategy for a CUA patient via intravenous combined with local treatment of hAMSCs, with speculated mechanisms including the inhibition of vascular calcification, the stimulation of neovascularization and myogenesis, as well as antiinflammation, immunoregulatory actions, and re-epithelialization 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This study is less relevant because it did not subcategorize patients on dialysis; the primary objective was to investigate the prevalence of thrombotic disorders in patients with calciphylaxis Carter et al discussed a case report of a patient with recalcitrant calciphylaxis affecting nearly 50% of both legs, which responded to daily subcutaneous unfractionated heparin therapy. 4 However, a clinical decision for our patient cannot be based on a case report.…”
mentioning
confidence: 98%